Penguatan Komunikasi Digital Berbasis OpenSID Untuk Meningkatkan Kualitas Pelayanan Publik di Nagari Durian Tinggi Kabupaten Pasaman: Strengthening OpenSID-Based Digital Communication to Enhance the Quality of Public Services in Nagari Durian Tinggi, Pasaman Regency - Yesi Puspita; Emeraldy Chatra; Ilham Havifi; Robi Jaya Putra (BULETIN ILMIAH NAGARI MEMBANGUN, 2026)
Digital transformation has become a strategic priority for improving public service delivery, transparency, and community participation in local governance. However, many rural administrative units (nagari) in Indonesia continue to face limitations in digital infrastructure and information management, reducing the accessibility and quality of public services. This community engagement program aimed to develop a local wisdom-based digital information system for Nagari Durian Tinggi to improve public information services, strengthen administrative capacity, and promote participatory governance. The program employed a participatory community engagement approach involving needs assessment, stakeholder consultation, website development using the OpenSID platform, database preparation, capacity-building workshops for nagari officials, and technical assistance for website management and maintenance. Program implementation emphasized the integration of local wisdom into digital content while enhancing the technological competence of local administrators. The program resulted in the establishment of an operational nagari website featuring a comprehensive village profile, public service information, governance data, and community development content. Capacity-building activities improved the digital literacy and technical skills of nagari officials, enabling more effective website management and public information dissemination. The digital platform also increased community access to government information, encouraged public participation in local development, and supported more transparent and efficient public services. Overall, the program demonstrates that a local wisdom-based village information system can strengthen digital governance, improve public service quality, and contribute to sustainable community development in rural areas.